2019
DOI: 10.1136/bmjoq-2018-000580
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a pharmacist intervention at an intensive care rehabilitation clinic

Abstract: ObjectiveWhile disruptions in medications are common among patients who survive critical illness, there is limited information about specific medication-related problems among survivors of critical care. This study sought to determine the prevalence of specific medication-related problems detected in patients, seen after critical care discharge.DesignConsecutive patients attending an intensive care unit (ICU) follow-up programme were included in this single-centre service evaluation.SettingTertiary care region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Intensive Care Syndrome: Promoting Independence and Return to Employment (InS:PIRE) is a 5-week rehabilitation program for ICU survivors. Previous research has described this program ( 4 6 ). Participants were invited between 4 and 12 weeks after hospital discharge.…”
Section: Methodsmentioning
confidence: 99%
“…Intensive Care Syndrome: Promoting Independence and Return to Employment (InS:PIRE) is a 5-week rehabilitation program for ICU survivors. Previous research has described this program ( 4 6 ). Participants were invited between 4 and 12 weeks after hospital discharge.…”
Section: Methodsmentioning
confidence: 99%
“…Because intensive care units (ICUs) are complex for patients and medications, the risk of prescribing errors and related adverse drug events (ADE) is high 1–3 . An adverse drug event, on the other hand, may be associated with the need for extra treatment, extended hospital stay, morbidity and mortality, and causes extra healthcare costs 2,4 .…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…Clinical pharmacy services to patient care based on pharmaceutical care principles contribute to improved therapeutic outcomes and the resolution of drug‐related issues such as drug compliance with indications, doses, side effects/toxicity, blood level monitoring, route of administration, interactions, and incompatibilities 5 . Studies also have shown that the frequency of AKI and other drug‐related problems observed in the clinic decreases with the involvement of the clinical pharmacist in the healthcare team 6–9 . However, no study is available in the literature showing the role of the clinical pharmacist in the prevention of AKI that can be observed in patients treated in the ICU and in improving the clinical outcomes of AKI.…”
Section: What Is Known and Objectivementioning
confidence: 99%